ANALISIS PROKSIMAT KERUPUK DAUN JERUJU DARI TANAMAN JERUJU (Acanthus ilicifolius) - Lily Novianty; Siti Nurlani Harahap; Dewi Novina Sukapiring (Universitas Cokroaminoto Palopo, 2023)
Proximate analysis is an analysis performed to determine the nutritional value contained in a food or processed food. This study aims to determine the water content, protein content, fat content, ash content and carbohydrate content of Jeruju leaf crackers. The method used in this research was an experimental method in the laboratory by analyzing the water content, protein content, fat content, ash content and protein content of Jeruju leaf crackers. From the research conducted, the water content results for the S1 treatment were 3.17 + 0.12; S2 is 6.58 + 0.01 and S3 is 6.51 + 0.53. The resulting protein content for the S1 treatment was 28.65 + 0.52; S2 of 31.78 + 0.53; S3 is 23.97 + 1.05. The resulting fat content for the S1 treatment was 24.49 + 0.06; S2 is 19.74 + 0.01 and S3 is 21.64 + 0.06. The resulting ash content for the S1 treatment was 2.12 + 0.01; S2 is 1.4 + 0.01 and S3 is 1.39 + 0.02. The resulting carbohydrate content for the S1 treatment was 41.55 + 0.5; S2 is 40.46 + 0.5 and S3 is 46.47 + 1. Analysis of water content, protein content and ash content in Jeruju leaf crackers decreased in value while for fat content and carbohydrate content increased the levels if the concentration of Jeruju leaf extract was added to the sample more and more